Investigation of Electric Parameters of Round Thyristors - Marcinkevičius, A.; Višniakov, E.; Jasonis, V. (Elektronika ir Elektrotechnika, 2005)
Dependences of forward and backward voltages of round thyristors on the size of boundary angles and the depth of diffusion junctions are considered. The obtained experimental investigation results confirm that the first angle formed in the sandblasting has more influence on the thyristor backward breakdown voltage at high temperature. It is experimentally confirmed that in order to obtain the lower electric field strength on the structure surface and a high breakdown voltage, the first angle should be decreased. The criterion of the second angle formation – the pn junction distance from the first angle – is chosen. The choice of the grinding time depends on the Ga or GaAl diffusion depth. It is determined that the formed second angle has influence on the forward breakdown voltage. The tendencies of the breakdown voltage variation by changing the grinding time of the second angle have been analyzed. The volt-ampere characteristics of breakdown voltages measured under normal conditions and at high temperature are presented. The influence of etching time of the thyristor surface on the breakdown voltage has been investigated. It is determined that the etching time has a larger influence on electric parameters during measurements at high temperature. It should be noted that the backward breakdown voltage can be improved by increasing the etching time of the first angle. The dependence of voltage on the open thyristor on the depth of the gallium diffusion pn junction has been investigated. Ill. 13, bibl. 3 (in Lithuanian; summaries in Lithuanian, English and Russian).